With-Ing: A Psychotherapy of Love - Olthuis, James H. (Journal of psychology and theology, 2006)
In this article the author sets out, in the first place, to sketch in the fundamentals of an anthropological model centered in God's creative and redeeming love. Secondly, the article seeks to develop a relational model of the psychotherapeutic process that flows out of and is congenial with this emphasis on love of God, neighbor, and self. The author suggests that the fundamental biblical affirmation of God's loving presence with creation—life-giving, forgiving, suffering with, and renewing—evokes and supports a “relational” model of psychotherapy as fundamentally a relational process of “with-ing.”